Biomechanical report for the IAAF World Indoor Championships 2018 60m women - Walker, J.; Tucker, C.; Paradisis, G.; Bezodis, I.; Bissas, A.; Merlino, S. (Leeds Becket University; Carnegie School of Sports, 2019)
The women`s 60 m sprint took place on the evening of Friday 2nd March. The final was to be a tight contest, as all eight finalists were coming into the competition with reasonably good form. Jamaica`s Elaine Thompson was a potential favourite, having run a personal best of 6.98 s in Birmingham one year previous. Murielle Ahouré (Ivory Coast) would also be a favourite for the race as the current world leader in the 60 m sprint. Indeed, Ahouré took the gold medal in convincing fashion. With a new world leading time of 6.97 s (tied-sixth all-time), Ahouré saw off her opponents by at least 0.08 s. Ahouré`s compatriot Marie-Josée Ta Lou took the silver medal, as she did in the World Outdoor Championships in London 2017. Mujinga Kambundji (Switzerland) took the bronze medal ahead of Elaine Thompson.